2018
DOI: 10.1016/j.aott.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The age dependent change in the incidence of calcaneal spur

Abstract: ObjectiveThe aim of the present study was to evaluate the association between the calcaneal spur incidence and age, gender and side.MethodsLateral ankle X-rays of 1335 patients (550 (41.2%) females and 758 (58.8) males; mean age: 46.5 ± 13.5 years) who referred to our hospital because of trauma were reviewed. Incidence of plantar calcaneal spur, posterior calcaneal spur and association of such incidences with age, gender and side were all evaluated.ResultsIncidences of plantar calcaneal spur and posterior calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 10 publications
0
26
3
1
Order By: Relevance
“…There is a higher prevalence of posterior calcaneal spurs as compared to inferior as reported by Beytemur et al 6 However our study showed a higher prevalence of…”
Section: Resultscontrasting
confidence: 70%
See 3 more Smart Citations
“…There is a higher prevalence of posterior calcaneal spurs as compared to inferior as reported by Beytemur et al 6 However our study showed a higher prevalence of…”
Section: Resultscontrasting
confidence: 70%
“…Similar results have been demonstrated by Johal et al 13 Inferior calcaneal spurs were more common in women according to Toumi et al 5 In the present study, there was an insignificant variation in the prevalence of calcaneal spur according to both genders. Incidence of calcaneal spurs have been reported as being higher in females by Vulcano et al 9 However, Beytemur et al 6 shows no significant association between prevalence of calcaneal spurs and gender.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The observed enthesophytes might be an example that in certain cases this metaplasia might happen to a greater extent than 'normally' , again being closely connected to the structural organization of the tendons (in the given study the AT). Supporting this, the prevalence of calcaneal spurs was shown to increase with age with no sex-dependency 16,17 . Reciprocally, the observed differences in colour intensity within the superficial calcaneal regular trabeculae itself might be an indication that the load distribution is irregular when mechanically strained.…”
Section: Discussionmentioning
confidence: 76%